Development of Inhalable ATRA-Loaded PLGA Nanoparticles as Host-Directed Immunotherapy against Tuberculosis - Ahmad Z. Bahlool; Sarinj Fattah; Andrew O'Sullivan; Brenton Cavanagh; Ronan MacLoughlin; Joseph Keane; Mary P. O'Sullivan; Sally-Ann Cryan (MDPI AG, 2022)
Developing new effective treatment strategies to overcome the rise in multi-drug resistant tuberculosis cases (MDR-TB) represents a global challenge. A host-directed therapy (HDT), acting on the host immune response rather than Mtb directly, could address these resistance issues. We developed an HDT for targeted TB treatment, using All Trans Retinoic Acid (ATRA)-loaded nanoparticles (NPs) that are suitable for nebulization. Efficacy studies conducted on THP-1 differentiated cells infected with the H37Ra avirulent Mycobacterium tuberculosis (Mtb) strain, have shown a dose-dependent reduction in H37Ra growth as determined by the BACT/ALERT® system. Confocal microscopy images showed efficient and extensive cellular delivery of ATRA-PLGA NPs into THP-1-derived macrophages. A commercially available vibrating mesh nebulizer was used to generate nanoparticle-loaded droplets with a mass median aerodynamic diameter of 2.13 μm as measured by cascade impaction, and a volumetric median diameter of 4.09 μm as measured by laser diffraction. In an adult breathing simulation experiment, 65.1% of the ATRA PLGA-NP dose was inhaled. This targeted inhaled HDT could offer a new adjunctive TB treatment option that could enhance current dosage regimens leading to better patient prognosis and a decreasing incidence of MDR-TB.